Ayurvedic Management of Tamak Shwasa (Bronchial Asthma) in Child (International Journal of Ayurveda and Pharma Research, 2024)
Tamak Shwasa is a term that encompasses many illnesses together with shortness of breath as the main symptom. However we can also companion bronchial asthma with Tamak Shwasa due to the last four, 3 of them are incurable and the fourth is Kshudra Shwasa, which is resulting from overwork and overeating, it may be cured in a simple manner. Early onset is easy to treat, however the chronic condition is hard to deal with. In Ayurveda, the word Shwasa defines as a disease in itself as well as symptoms and issues of different diseases. Acharya Charaka describes Tamak Shwasa as a Yappya sort of contamination where in the patient has to depend on remedy for alleviation. Acharya Charak teaches different accurate thoughts approximately Tamak Shwasa. In this text a single case study of 10 years boy identified with Tamaka shwasa treated with Ayurvedic control like Shamana and Mrudu Shodhana given in details.